DESIGN AND BUILD PAVING BLOCK MAKING MACHINE WITH ECCENTRIC MOTOR VIBRATING SYSTEM - Edi Rande Padang (Sean Institute, 2022)
Paving blocks are one of the materials that are needed in rural and urban areas. Most paving blocks are produced by manual means which takes quite a long time. To overcome these obstacles, a paving block making machine is needed that can function efficiently. This research aims to design and make a paving block making machine with an eccentric motor vibrating system. The methodology used in this study is experimental research consisting of the planning stage, the design and manufacture stage, the testing and analysis stage and the finalization stage. The tests carried out include testing the speed in producing paving blocks. This research resulted in a paving block making machine with an eccentric motor vibrating system. The machine is made with frame, mold, press, mold lifting lever and press, eccentric vibrating transmission and gutter. This machine has a height of 1831 mm and a width of 917 mm and has a mold of 14 block-shaped pieces with a size of 20 cm x 10 cm. The mold and press are installed not permanently so that the mold or press can be replaced with another form. The use of this vibrator to compact the mixture. The machine consists of frame, mold, press, mold lifting lever and press, eccentric vibrating transmission and gutter. This machine has a height of 1831 mm and a width of 917 mm and has a mold of 14 block-shaped pieces with a size of 20 cm x 10 cm. The mold and press are installed not permanently so that the mold or press can be replaced with another form. From the tests carried out, 14 paving blocks were obtained with an average time of 2 minutes 23 seconds or 376 paving blocks/hour, Compared to manual work that produces 1 minute 1 paving block or 60 pieces of paving blocks/hour then, with this machine the production of paving blocks will increase.